Media Pembelajaran Anak Usia Dini Dengan Animasi Interaktif Berbasis ActionScript - Supriyadi Sandi (Jurnal Komunikasi, 2020)
Abstract – Early childhood education is a level of basic education  which  is  an educational effort aimed at children aged two years to six years, which is carried out through the provision of education to help growth, physical and spiritual development so that children have readiness to enter further education. Education is provided on the track formal, nonformal and informal. This research will make actionscript based education applications. In making this application, observation or direct observation is needed to find out how far the children receive the material given by the teacher in the classroomand what obstacles affect children's concentration in the problem. So that the application can match what is needed. Adobe Flash player is software that functions to run various kinds of multimedia files created in the Adobe Flash platform. This application was originally available for a variety of computer or mobile operating systems, including Adobe Flash Player for Android.Results of research produces educational  applications,as  a  means  to support the children's interest in learning outside of  school, at home. So that children do not miss the material given by  the  teacher  in  the  classroom. And material can be quickly accepted by children. Keywords : Learning Media, Letters and Numbers, Actionscrip